THE RELATIONSHIP BETWEEN ORGANIZATIONAL ACTIVITY AND THE LEVEL OF DEPRESSION AMONG STUDENTS IN INDONESIA: A CROSS-SECTIONAL STUDY - Wardani, Yuniar Laksmi Eka; Sa'adah, Irma Hanifatu; Sari, Jayanti Dian Eka (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: Students are free and want to innovate, but often experience stress and psychological problems due to academic and organizational responsibilities. According to the latest data, around 10.7% of Indonesia's population aged 15 years and over experience depression, and a survey of university students showed that 76% experience psychological pressure. Purpose: This study explored the relationship between the level of organizational activity and depression in sixth-semester public health students at the Faculty of Health, Medicine and Natural Sciences (FIKKIA) Universitas Airlangga. Methods: This research used quantitative methods and the CES-D instrument. The research design is a chi-square test with STATA software. Results: The results of the analysis showed that 45.83% of public health students who did not join organizations had moderate depression and 16.67% had very severe depression. Meanwhile, 40% of those who participated in the organization had moderate depression and 10% had very severe depression. Conclusion: Research shows there is no relationship between organizational activity and depression levels, with a value of (ρ=0.382 > 0.05). A recommendation to improve student well-being is to provide easily accessible counseling services so that students can understand and overcome their depression. Abstrak Latar Belakang: Mahasiswa merupakan individu yang bebas dan berkeinginan untuk berinovasi, namun sering kali mengalami stres dan masalah psikologis akibat tanggung jawab akademis dan organisasi. Menurut data terkini, sekitar 10,7% populasi Indonesia berusia 15 tahun ke atas mengalami depresi, dan survei terhadap mahasiswa menunjukkan bahwa 76% mengalami tekanan psikologis. Tujuan: Penelitian ini bertujuan untuk mengeksplorasi hubungan antara tingkat keaktifan organisasi dengan tingkat depresi mahasiswa kesehatan masyarakat semester VI di Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA) Universitas Airlangga. Metode: Penelitian ini menggunakan metode kuantitatif, dengan mengguakan instrumen CES-D. Desain penelitian berupa uji chi square dengan software STATA. Hasil: Hasil analisis menunjukkan mahasiswa kesehatan masyarakat yang tidak mengikuti organisasi, 45,83% memiliki depresi sedang dan 16,67% depresi sangat parah. Sementara yang mengikuti organisasi, 40% depresi sedang dan 10% depresi sangat parah. Kesimpulan: Penelitian menunjukkan tidak ada hubungan antara keaktifan organisasi dan tingkat depresi, dengan nilai (ρ=0,382 > 0,05). Rekomendasi untuk meningkatkan kesejahteraan mahasiswa adalah menyediakan layanan konseling yang mudah diakses, agar mahasiswa dapat memahami dan mengatasi depresi mereka.